Correlation Analysis of Sleep Quality and Youth Ischemic Stroke - Shunqing Zhang; Cheng Chang; Juan Zhang; Bo Song; Hui Fang; YuMing Xu (Behavioural Neurology)
Objective. To study risk factors related to ischemic stroke (IS) in youth and the influence of sleep quality on youth ischemic stroke incidence. Methods. 223 patients aged 18 to 45 years who were admitted to Puyang People’s Hospital from June 2011 to February 2013 with a first-ever ischemic stroke were selected as the research cases. 158 young people with a normal physical examination were selected as the control group. The Pittsburgh Sleep Quality Index (PSQI) questionnaire was used to analyse the correlation between sleep quality and youth IS incidence. The US National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (MRS) scores were used to assess cases’ state of illness and prognosis three months after IS. Results. Univariate and multivariate logistic regression analysis showed that the association of these risk factors with youth IS incidence, from highest to lowest, was hypertension, hyperlipidaemia, smoking history, high homocysteine, the quality of sleep, family history of stroke, and alcoholism. Poor sleep quality ranked fifth among all risk factors and was positively correlated with poor prognosis for youth IS patients. Conclusion. The results of this study showed that sleep quality is an important factor in the pathogenesis and prognosis of youth IS.